Painting in Canada - Lord, Barry; Montreal Expo 1967 (Montréal : [s.n.], 1967)
Barbeau, Marcel ; Bates, Maxwell Bennett ; Blazeje, Zbigniew ; Bloore, Ronald ; Borduas, Paul-Emile ; Breeze, Claude ; Brittain, Miller ; Bush, Jack ; Carr, Emily ; Chambers, John ; Clerk, Pierre ; Comfort, Charles ; Curnoe, Greg ; Fisher, Brian ; Gaucher, Yves ; Godwin, Ted ; Grauer, Sherry ; Harris, Lawren S. ; Horsman Varley, Frederick ; Humphrey, Jack ; Kiyooka, Roy ; Lemieux, Jean-Paul ; Lemoine FitzGerald, Lionel ; Levine, Les ; Macdonald, Jock ; McEwen, Jean ; McKay, Art ; Meredith, John ; Milne, David ; Molinari, Guido ; Onley, Toni ; Pellan, Alfred ; Riopelle, Jean-Paul ; Roberts, Goodridge ; Snow, Michael ; Tousignant, Claude ; Town, Harold ; Warkov, Esther ; Wieland, Joyce
biog. per kunstenaar
Engels
Painting in Canada, Canadian Government Pavilion, Expo 67, Montréal, 27.04. - 29.10.1967
boek
Keywords: Canada